Using Facebook® as iterative evaluation tool for the design and development of a virtual learning resource platform for Malaysian primary schools - Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal; Sahrir, Muhammad Sabri (Institute for Research Publications (IRP Journals), 2015)
The emergence of online educational courseware serves as an important addition to the teaching and learning aids of the digital generation. It is increasingly becoming the focus of researchers in designing and developing new and up-to-date educational aids that cater to the learning needs of 21st century learners as well as keeping in-line with the transformation of latest technologies. This chapter features a virtual Arabic learning tool prototype specifically designed for primary schools learners in Malaysia in providing an interactive and attractive learning aid in an online open-source platform. The innovative process of design and development begun with the literature analysis of 3 theories based on the work of Nation (2003), Prensky (2001) and Mayer (2001). The design and development of this game-based learning prototype are modeled on the methods and approaches of design and development research (Richey & Klein, 2007) or formerly known as developmental research (Richey, Klein & Nelson, 2004). The adapted method is also known as designed case (Reigeluth & Frick, 1999), design-based research (Reeves, 2006 & Herrington, et. al, 2007), formative research (Nieveen, 2007), and design research (Bannan-Ritland, 2003; Van der Akker, 2007). The ‘design principles’ are adapted from a study on the design and development of an online Arabic vocabulary learning games prototype among pre-university learners in IIUM by Muhammad Sabri (2011). This Arabic virtual learning tool prototype also enables teachers and students access to additional Arabic language learning aids that complement traditional learning methods. It facilitates Arabic learning enhancement through a compendium and a variety of open-sources learning tools such as the followings : a) E-book of Arabic text books, including story books for extra reading, b) Educational Arabic games, c) Audio learning aids (MP 3) in Arabic, d) Visual learning aids (MP 4) in Arabic, e) Online dictionary and translator for Arabic, f) Online chat-box for virtual discussion and synchronous learning, g) Arabic keyboard for PC without Arabic letters stickers, and h) Links of various websites in learning Arabic for children. The prototype provides a new learning experience for students who have been through traditional Arabic teaching and learning methods allowing engagement with an attractive, interesting, and interactive virtual learning environment. The prototype is still in its design and development phase and the feedbacks from teachers and users were analyzed via the famous online social networking website, Facebook ®. The URL for this prototype is http://ezarabic.net/v1/. This prototype won a bronze medal award in 2012 International Islamic University Malaysia Research, Invention, and Innovation Exhibition (IRIIE 2012) which was organised on 21-22 February 2012.